1-Deoxysphingolipids cause autophagosome and lysosome accumulation and trigger NLRP3 inflammasome activation. Issue 8 (3rd August 2021) - Lauterbach, Mario A.; Saavedra, Victor; Mangan, Matthew S. J.; Penno, Anke; Thiele, Christoph; Latz, Eicke; Kuerschner, Lars
ABSTRACT: 1-Deoxysphingolipids (deoxySLs) are atypical sphingolipids of clinical relevance as they are elevated in plasma of patients suffering from hereditary sensory and autonomic neuropathy (HSAN1) or type 2 diabetes. Their neurotoxicity is described best but they inflict damage to various cell types by an uncertain pathomechanism. Using mouse embryonic fibroblasts and an alkyne analog of 1-deoxysphinganine (doxSA), the metabolic precursor of all deoxySLs, we here study the impact of deoxySLs on macroautophagy/autophagy, the regulated degradation of dysfunctional or expendable cellular components. We find that deoxySLs induce autophagosome and lysosome accumulation indicative of an increase in autophagic flux. The autophagosomal machinery targets damaged mitochondria that have accumulated N-acylated doxSA metabolites, presumably deoxyceramide and deoxydihydroceramide, and show aberrant swelling and tubule formation. Autophagosomes and lysosomes also interact with cellular lipid aggregates and crystals that occur upon cellular uptake and N-acylation of monomeric doxSA. As crystals entering the lysophagosomal apparatus in phagocytes are known to trigger the NLRP3 inflammasome, we also treated macrophages with doxSA. We demonstrate the activation of the NLRP3 inflammasome by doxSLs, prompting the release of IL1B from primary macrophages. Taken together, our data establish an impact of doxSLs on autophagy and link doxSL pathophysiology to inflammation and the innate immune system. Abbreviations : alkyne-doxSA: (2S, 3R)-2-aminooctadec-17yn-3-ol; alkyne-SA: (2S, 3R)-2- aminooctadec-17yn-1, 3-diol; aSA: alkyne-sphinganine; ASTM-BODIPY: azido-sulfo-tetramethyl-BODIPY; CerS: ceramide synthase; CMR: clonal macrophage reporter; deoxySLs: 1-deoxysphingolipids; dox(DH)Cer: 1-deoxydihydroceramide; doxCer: 1-deoxyceramide; doxSA: 1-deoxysphinganine; FB1: fumonisin B1; HSAN1: hereditary sensory and autonomic neuropathy type 1; LC3: MAP1LC3A and MAP1LC3B; LPS: lipopolysaccharide; MEF: mouse embryonal fibroblasts; MS: mass spectrometry; N3 635P: azido-STAR635P; N3 Cy3: azido-cyanine 3; N3 picCy3: azido-picolylcyanine 3; NLRP3: NOD-like receptor pyrin domain containing protein 3; P4HB: prolyl 4-hydroxylase subunit beta; PINK1: PTEN induced putative kinase 1; PYCARD/ASC: PYD and CARD domain containing; SPTLC1: serine palmitoyltransferase long chain base subunit 1; SQSTM1: sequestosome 1; TLC: thin layer chromatography.